Fractional Anisotropy in Selected, Motor-Related White Matter Tracts and Its Cross-Sectional and Longitudinal Associations With Motor Function in Healthy Older Adults - Oschwald, Jessica; Mérillat, Susan; Jäncke, Lutz; Seidler, Rachael D. (Frontiers in Human Neuroscience, 2021)
BACKGROUND. While it is well-known that deficits in motor performance and brain structural connectivity occur in the course of healthy aging, it is still unclear if and how these changes are related to each other. Evidence from cross-sectional studies suggests that white matter (WM) microstructure is positively associated with motor function in healthy older adults. However, longitudinal data are needed to estimate whether similar associations can be found between trajectories of change in WM microstructure and motor function, and to disentangle the directionality of their relation. The current study addresses this gap by investigating longitudinal changes in WM microstructure and motor function, and the cross-sectional (level-level) and longitudinal (level-change, change-change) association between these two domains. METHOD. We used multiple-occasion data (covering 4 years) from a large sample (N = 231) of healthy older adults from the Longitudinal Healthy Aging Brain (LHAB) database. To measure WM microstructure, we used diffusion-weighted imaging data from three WM tracts (forceps minor, FMIN; superior longitudinal fasciculus, SLF; corticospinal tract, CST). Motor function was measured via two motor speed tests (grooved pegboard, finger tapping) and one motor strength test (grip force test), separately for the left and the right hand. The statistical analysis was conducted with longitudinal growth curve models in the structural equation modeling framework. RESULTS. The results revealed longitudinal decline and negative cross-sectional age-associations for WM microstructure in the FMIN and SLF, and for motor function in all tests, with a higher vulnerability for left than right hand motor performance. Regarding cross-domain associations, we found a significant positive level-level correlation among WM microstructure in the FMIN with motor speed. The SLF and CST were not correlated with motor performance measures, and none of the level-change or change-change associations were significant. Our findings are in alignment with the idea that neural control of movement is supported by structures outside of the sensorimotor system in older adults.